Non-alcoholic fatty liver disease: comparative assessment of diagnostic and treatment approaches in the Russian Federation and People’s Republic of China - M. Ch. Semenistaya; Fan Jian-Gao; O. B. Velichenko; Ye. A. Kuznetsova; Ch. S. Pavlov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present comparative assessment of diagnostic and treatment approaches at non-alcoholic fatty liver disease (NAFLD) in the Russian Federation and People’s Republic of China. Summary. NAFLD is the leading disease entity among the other chronic liver diseases in the countries of various regions of the world, at the present time it is considered to be one of the main causes for cryptogenic liver cirrhosis development. The pathogenesis of NAFLD closely correlates to both hepatic and cardiovascular involvement that significantly influences both treatment choice and life prognosis. According to the international clinical guidelines, NAFLD screening methods should include elastometry and serological tests to rule out severe liver fibrosis (F> 2). Liver biopsy is carried out at contradictory data of liver elastometry and serological fibrosis markers. Treatment of NAFLD should integrate the range of measures including correction of patients dietic habits and physical activity up to pharmacological treatment. Pharmacotherapy is recommended in the case of nonalcoholic steatohepatitis (NASH) progression (bridging fibrosis ³ F2 and cirrhosis), as well as the earlier stages of NASH with two and more fibrosis progression risk factors (age over 50 years, diabetes mellitus, metabolic syndrome, alanine transaminase elevation). Bicyclol is a drug developed in Materia Medica institute of Academy of medical sciences of China. The study is carried on by Chinese physicians have demonstrated efficacy of the drug for treatment of chronic liver diseases of various etiology, along with its antiinflammatory and antifibrotic properties. The drug registration studies conducted in the Russian Federation revealed high clinical performance of Bicyclol. Conclusion. Etiological and pathogenetic features of NAFLD require diverse therapeutic actions from dietic recommendations and physical activity correction of the prescription of various pharmacological agents. Results of clinical efficacy estimation of the new drug Bicyclol in the Russian market, that it was developed in the People’s Republic of China demonstrate reduction of severity of inflammation, steatosis, fibrosis and decrease of NAFLD activity scores.